The Relationship between Fatigue and Poor Sleep Quality and the Incidence of Postpartum Blues among Postpartum Mothers - Annisa Jasmin; Lina Ayu Marcelina (NERS Jurnal Keperawatan, 2026)
Postpartum blues is a common mood disorder experienced by mothers after childbirth and has a high prevalence in Indonesia, potentially affecting the well-being of both the mother and the infant. Although numerous studies have explored postpartum blues, research specifically examining postpartum maternal fatigue remains limited. This study aimed to identify the relationship between fatigue and sleep quality with the incidence of postpartum blues among postpartum mothers. A cross-sectional study design was employed, involving 120 respondents selected using a non-probability sampling method. The study was conducted at the Kalideres Sub-district Health Center, a primary health care facility located in the Kalideres sub-district, West Jakarta, Indonesia. Data were collected using standardized and validated instruments, namely the Postpartum Fatigue Scale (PFS) to assess fatigue, the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality, and Stein’s Maternity Blues Scale (MBS) to evaluate the incidence of postpartum blues. Data were analyzed using univariate and bivariate statistical tests. The results showed that 71.7% of respondents experienced high fatigue, 69.2% had poor sleep quality, and 76.7% exhibited symptoms of postpartum blues. Statistical analysis demonstrated a significant association between fatigue and the incidence of postpartum blues (p < 0.001), as well as between sleep quality and postpartum blues (p < 0.001). This study concludes that high fatigue and poor sleep quality are significantly associated with the incidence of postpartum blues. Therefore, education and supportive interventions for postpartum mothers are recommended to help manage fatigue and improve sleep quality, with active involvement from families and health professionals to prevent postpartum blues.